When God Smites: Talking with Students about the Violence of God in Scripture - Seibert, Eric A. (Teaching theology and religion, 2014)
This article emphasizes the need for religious educators to address the issue of divine violence in Scripture with students, and it offers various pedagogical strategies for doing so. The focus is on violent Old Testament texts, with special attention given to the issue of Canaanite genocide. A general framework for structuring class time around divine violence in Scripture is proposed which includes (1) encouraging students to encounter violent biblical texts firsthand, (2) helping them understand why people find these passages problematic, and (3) offering various options for dealing with the potential problems these passages raise. In the second half of the article, significant attention is devoted to a number of practical considerations that should be taken into account when talking about this sensitive issue in class. A brief word about assessment is offered at the end.